Effect of Degradation During Multiple Primary Mechanical Recycling Processes on the Physical Properties and Biodegradation of Commercial Pla-Based Water Bottles - Velasquez, E (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
For sustainable development aligned with circular economy principles, the recycling of biopolymers such as polylactic acid (PLA) is of growing interest. In this study, the effect of primary recycling through repeated mechanical reprocessing was investigated. PLA water bottle preforms were subjected to six consecutive extrusion cycles, and changes in its molecular structure and physical properties were evaluated. Structural analysis revealed a progressive degradation, evidenced by a great reduction in the molar mass and increase in the melt flow index, attributed both to the chain scission derived from the thermal degradation and shear stresses of the extrusion process, and hydrolysis at the ester linkage of the polymer. Recycled samples exhibited a darkening of the color and a continuous decrease in thermal stability. After six reprocessing cycles, PLA crystallinity increased from 6.9 to 39.5%, the cold crystallization process disappeared, and molecular weight reduced by up to 40%. Barrier properties were highly affected after reprocessing and by the increase in relative humidity. Biodegradation tests revealed that crystallinity affected considerably the biodegradation rate of PLA. Although the molecular weight was considerably reduced during reprocessing, the biodegradation was slowed down. These findings provide insights into the limitations and potential of mechanically recycled PLA for future material applications. © 2025 by the authors.